"All Stars" for at-risk middle school students in an afterschool setting: a pilot program. (December 2014) - Cummings, Madeline; Whitlock, Alyssa; Draper, Michele; Renschler, Lauren; Bastian, Kayla; Cox, Carolyn C.; Visker, Joseph D.
Abstract Introduction: The evidenced-based program, All Stars, usually conducted in the in-school setting and taught by classroom teachers; was implemented in an afterschool setting for at-risk middle school students by local university student volunteers. The classroom-based program was moved to the after-school setting in this study in order to target the most at-risk students, and university student volunteers served as instructors to decrease program costs. Methods: Middle school students enrolled in an afterschool program for the most academically and socially at-risk participated in an evidence-based substance abuse prevention program and study as a part of their overall afterschool curriculum. The Pre-Post Post All Stars Student Survey was used as the data collection instrument and included 45 demographic, behavior, and core mediator Likert-scale questions. A series of paired samples t-tests were used to assess pre-post differences in the following: Commitment to Avoid Risky Behaviors, Normative Beliefs, and Lifestyle Incongruence. Results: At the conclusion of the program, participants' lifestyle incongruence about substance abuse improved significantly, their commitment to avoid risky behaviors improved, but their normative beliefs decreased. Discussion/conclusion: For those youth at high-risk, providing the program in the afterschool setting and using non-classroom teachers as instructors does seem to have potential for successful program delivery.